Prokaryotic respiration and production in the meso- and bathypelagic realm of the eastern and western North Atlantic basin - Reinthaler, Thomas; Aristegui, J.; Robinson, Carol; Arístegui, Javier; Lebaron, Philippe; Herndl, Gerhard J.; Aken, Hendrik van; Veth, Cornelis (Limnology and Oceanography, 2018)
We measured prokaryotic production and respiration in the major water masses of the North Atlantic down to a depth of 4,000 m by following the progression of the two branches of North Atlantic Deep Water (NADW) in the oceanic conveyor belt. Prokaryotic abundance decreased exponentially with depth from 3 to 0.4 3 105 cells mL21 in the eastern basin and from 3.6 to 0.3 3 105 cells mL21 in the western basin. Prokaryotic production measured via 3H-leucine incorporation showed a similar pattern to that of prokaryotic abundance and decreased with depth from 9.2 to 1.1 mmol C m23 d21 in the eastern and from 20.6 to 1.2 mmol C m23 d21 in the western basin. Prokaryo tic respiration, measured via oxygen consumption, ranged from about 300 to 60 mmol C m23 d21 from ,100 m depth to the NADW. Prokaryotic growth efficiencies of ,2% in the deep waters (depth range 1,200–4,000 m) indicate that the prokaryotic carbon demand exceeds dissolved organic matter input and surface primary production by 2 orders of magnitude. Cell-specific prokaryotic production was rather constant throughout the water column, ranging from 15 to 32 3 1023 fmol C cell21 d21 in the eastern and from 35 to 58 3 1023 fmol C cell21 d21 in the western basin. Along with increasing cell-specific respiration towards the deep water masses and the relatively short turnover time of the prokaryotic community in the dark ocean (34–54 d), prokaryotic activity in the meso- and bathypelagic North Atlantic might be higher than previously assumed. 1273 1262 3,287 Q1 SCIE